Group 2 innate lymphoid cells in bone marrow regulate osteoclastogenesis in a reciprocal manner via RANKL, GM-CSF and IL-13. (9th September 2021) - Momiuchi, Yoshiki; Motomura, Yasutaka; Suga, Emiko; Mizuno, Hiroki; Kikuta, Junichi; Morimoto, Akito; Mochizuki, Miho; Otaki, Natsuko; Ishii, Masaru; Moro, Kazuyo
Abstract: Group 2 innate lymphoid cells (ILC2s) are tissue-resident cells that play different roles in different organs by sensing surrounding environmental factors. Initially, it was thought that ILC2s in bone marrow (BM) are progenitors for systemic ILC2s, which migrate to other organs and acquire effector functions. However, accumulating evidence that ILC2s differentiate in peripheral tissues suggests that BM ILC2s may play a specific role in the BM as a unique effector per se . Here, we demonstrate that BM ILC2s highly express the receptor activator of nuclear factor κB ligand (RANKL), a robust cytokine for osteoclast differentiation and activation, and RANKL expression on ILC2s is up-regulated by interleukin (IL)-2, IL-7 and all-trans retinoic acid (ATRA). BM ILC2s co-cultured with BM-derived monocyte/macrophage lineage cells (BMMs) in the presence of IL-7 induce the differentiation of tartrate-resistant acid phosphatase (TRAP)-positive osteoclasts in a RANKL-dependent manner. In contrast, BM ILC2s stimulated with IL-33 down-regulate RANKL expression and convert BMMs differentiation into M2 macrophage-like cells rather than osteoclasts by granulocyte macrophage colony-stimulating factor (GM-CSF) and IL-13 production. Intravital imaging using two-photon microscopy revealed that a depletion of ILC2s prominently impaired in vivo osteoclast activity in an IL-7 plus ATRA-induced bone loss mouse model. These results suggest that ILC2s regulate osteoclast activation and contribute to bone homeostasis in both steady state and IL-33-induced inflammation. Abstract : How ILC2s regulate osteoclastogenesis